1995
DOI: 10.1152/ajprenal.1995.269.1.f1
|View full text |Cite
|
Sign up to set email alerts
|

Function and structure of H-K-ATPase in the kidney

Abstract: The present review summarizes recent functional and structural evidence indicating that the kidney possesses at least one and probably more than one isoform of a proton- and potassium-activated adenosinetriphosphatase (H-K-ATPase). Functional studies have examined in detail the mechanism of luminal acidification and K/Rb absorption by the outer medullary collecting duct (OMCD) from the inner stripe, a high-capacity distal site of urinary acidification. These studies indicate that the mechanism of proton secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 0 publications
3
77
1
Order By: Relevance
“…Recent studies have demonstrated that KCNQ1 is also present in parietal cells (13), which was confirmed here, and is necessary for gastric acid secretion (10,34). Isoforms of H (1, 2, 28, 38, 43) and contribute to acid secretion, similar to the gastric parietal cell (44). The cooperation of an apical K ϩ channel with H ϩ -K ϩ -ATPase transport has been proposed in previous studies from our laboratory (44,46).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recent studies have demonstrated that KCNQ1 is also present in parietal cells (13), which was confirmed here, and is necessary for gastric acid secretion (10,34). Isoforms of H (1, 2, 28, 38, 43) and contribute to acid secretion, similar to the gastric parietal cell (44). The cooperation of an apical K ϩ channel with H ϩ -K ϩ -ATPase transport has been proposed in previous studies from our laboratory (44,46).…”
Section: Discussionsupporting
confidence: 85%
“…Isoforms of H (1, 2, 28, 38, 43) and contribute to acid secretion, similar to the gastric parietal cell (44). The cooperation of an apical K ϩ channel with H ϩ -K ϩ -ATPase transport has been proposed in previous studies from our laboratory (44,46). Under K ϩ -replete conditions, apical H ϩ -K ϩ -ATPase transport in the rabbit CCD is accompanied by apical K ϩ recycling, resulting in proton secretion without transepithelial K ϩ absorption (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…*Significantly different from basal condition, applying to the increase in H flux after incubation at pH 6.8. Ϫ 3 found that 35% of the rate was due to the P-type H These data differ somewhat from those of Wingo's laboratory (26,27,49), which show ‫ف‬ 70% of HCO flux is sensitive to inhibition of H ϩ ,K ϩ -ATPase, and only 30% to inhibition of the vacuolar H ϩ -ATPase. The results do agree in that the combination of inhibitors totally eliminates net HCO absorption (27), indicating that the vacuolar H ϩ -ATPase and the P-type H ϩ ,K ϩ -ATPase are the two main proton pumps in the OMCD of the inner stripe.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, mammalian renal epithelial cells have H ϩ -K ϩ -ATPases, as well as NHEs, V-ATPases, along their luminal membranes. These transporters are divided further into isoforms that are thought to function in different nephron segments and may be stimulated by different pH and/or electrolyte imbalances (257, 567,691,813,814). It has recently been demonstrated that a transcript homologous to an H ϩ -K ϩ -ATPase is expressed in the gills of elasmobranchs.…”
Section: H ϩ -K ϩ -Atpasementioning
confidence: 99%